Security in process migration systems - Echaiz, Javier (2005)
A loosely coupled distributed system is composed by nodes, usually heterogenous, connected by a network. These systems have enormous aggregate computing potential. However most of this potential is not realized unless the underlying software is able to implement the concept of single system image (SSI) on the physically distributed system. This way the resources belonging to a node could be accessed transparently from any other node. This paper discusses the issues of a process migration protocol as an essential component of a distributed system and its extension to the grid computing paradigm. The security issues are specially considered.